Sobre la invisibilización y las representaciones de lo indígena en el Perú Algunas reflexiones sobre problemas centrales en la construcción social de la ciudadanía - Molinari Morales, Tirso Aníbal (2008)
This work reflects about the complex relation between the indigenous culture its representations, self-representations and new meanings, the difficulty of the intercultural openings, the fingerprint of the oligarchical mentality and the diverse significances of what is national and modern in Peru